Evaluation of Physicochemical Attributes of Three Cauliflower (Brassica oleracea var. botrytis L.) Varieties (Journal of the Bangladesh Agricultural University, 2025)
The study was conducted to determine the physico-chemical attributes of three cauliflower genotypes of different colors (white, yellow, and purple).  The experiment was conducted from February to March 2024 following a completely randomized design (CRD) with seven replications. Statistically, physical attributes did not vary among the three cauliflower genotypes. However, the yellow cauliflower had the highest weight, height, and percent edible parts numerically, and the purple cauliflower had the highest diameter and thickness of curd. The three cauliflowers have different chemical attributes. The maximum values in vitamin C (83.633 mg∕100g), titratable acidity (0.16%), and carotenoids (0.0266 mg∕100g) were found in yellow cauliflower. The purple cauliflower had the highest riboflavin content (0.5746 mg∕100g), while the white cauliflower had the lowest riboflavin content (0.3944 mg∕100g). The purple cauliflower was also superior in terms of anthocyanin (0.9349 mg∕100g) and flavonoid contents (0.3943 mg∕100g). The findings provide a comprehensive understanding of the differences in nutritional and physical properties among cauliflower genotypes, which could help consumers and farmers.J Bangladesh Agril Univ 23(3): 419–424, 2025